2020
DOI: 10.7150/thno.47432
|View full text |Cite
|
Sign up to set email alerts
|

BET inhibitor suppresses melanoma progression via the noncanonical NF-κB/SPP1 pathway

Abstract: Background: Bromodomain and extra-terminal domain (BET) inhibitors have shown profound efficacy against hematologic malignancies and solid tumors in preclinical studies. However, the underlying molecular mechanism in melanoma is not well understood. Here we identified secreted phosphoprotein 1 (SPP1) as a melanoma driver and a crucial target of BET inhibitors in melanoma. Methods: Bioinformatics analysis and meta-analysis were used to evaluate the SPP1 expression in normal tis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
63
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 77 publications
(66 citation statements)
references
References 64 publications
1
63
0
2
Order By: Relevance
“…Inhibitors targeting EZH2 also induce the re-expression of tumor suppressors associated with enhanced patient survival [ 17 ]. Past studies have also revealed that JQ1 can be used to treat vemurafenib-resistant melanoma cells [ 18 ] and that BET inhibitors effectively suppress melanoma progression via the noncanonical NF-κB/SPP1 pathway [ 19 ]. However, information regarding the role of TP-472 in melanoma therapy remains limited.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Inhibitors targeting EZH2 also induce the re-expression of tumor suppressors associated with enhanced patient survival [ 17 ]. Past studies have also revealed that JQ1 can be used to treat vemurafenib-resistant melanoma cells [ 18 ] and that BET inhibitors effectively suppress melanoma progression via the noncanonical NF-κB/SPP1 pathway [ 19 ]. However, information regarding the role of TP-472 in melanoma therapy remains limited.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, PAT-1251 (newly designated GB2064), which targets LOXL2, has been used in phase 1 clinical trials for the treatment of lung disease as well as metastatic breast cancer [ 48 , 49 ]. Studies have also shown that SPP1 is an important target of BET inhibitors, which can effectively inhibit the growth of melanoma cells [ 19 ]. A recent study identified CA-074Me as a specific cell-permeable CTSB inhibitor [ 50 ] and small-molecule inhibitor diethyl-pythiDC that targets P4HA1 has been used for treating colorectal cancer [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…The ability of BET inhibitor targeting oncogenic pathways in different cancers endows its extensive clinical applications, and increasing number of FDA-approved BET inhibitors have been studied in variety of cancers (31)(32)(33). In our previous studies, we explored the ability of a potent BRD4 inhibitor NHWD-870 shows great tumor suppressive potential in multiple solid tumors by depleting phosphorylated BRD4 and c-MYC (8,9). In the current study, we further explored the anti-osteosarcoma activity of NHWD-870 and the related mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…The significant clinical value of BET targeted therapy has been proven, and several BET inhibitors have been designed and applied ( 5 7 ). In our previous study, we reported the discovery and characterization of the novel BET inhibitor NHWD-870, and mechanism by which BRD4 inhibition suppresses tumor growth ( 8 , 9 ). The present study aimed to further explore the effects of NHWD-870 in osteosarcoma and the related mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…So far, several BETis, such as thienodiazepine JQ1, I-BET151/GSK1210151A, I-BET762/GSK525762, ABBV-075, PLX51107, ODM-207, and ZEN003694 have shown encouraging clinical outcomes with tolerable toxicity and increased efficiency in various tumor types [ 260 , 261 ]. BRD4 is a notorious BET family member that is consistently reported to be amplified or overexpressed in human melanoma lines and primary tumors [ 262 ]. Notably, one study suggested that BETi treatments significantly affected melanoma cell proliferation in vitro and tumor growth and metastasis in vivo due to the downregulation of genes involved in cell cycle progression (SKP2, ERK1, and c-MYC) and concomitant accumulation of cyclin-dependent kinase inhibitors (p21 and p27).…”
Section: Epigenetics-based Therapies For CMmentioning
confidence: 99%